Tongue Mucoceles: a retrospective clinic-pathological evaluation of 240 cases - Romeo Patini; Michele Giuliani; Gioele Gioco; Mariateresa Tranfa; Vito Carlo Alberto Caponio; John Fantasia; Carlo Lajolo (BMC, 2023)
Abstract Background Minor salivary glands can be found in the ventral and anterior part of the tongue; these glands can rarely develop mucoceles that, due to their rarity and their unusual clinical appearance, may present an interesting differential diagnosis. Mucoceles appear as an exophytic, sometimes pedunculated, lesion, which is a feature that is due to the absence of a capsule; thus, the glands are right beneath the mucosa and over the muscle tissue. The aim of this article is to retrospectively present and discuss the anatomy, pathology, clinical features and therapy of several cases of Blandin-Nunh mucoceles collected from two different institutions. Methods A retrospective case review was carried out in two university institutions, retrieving all cases of tongue mucoceles from 1999 to today. Two oral pathologists reviewed all the slides, confirming the diagnosis. Demographic data of the patient, anatomic location and clinical appearance were retrieved from clinical charts, together with the type of surgical procedure and possible relapses. Results A total of 240 cases of tongue mucoceles were gathered from the archives: the mean age was 22 years (DS = 14,7; Range 2-83), 126 were females (52,5%, mean age 22,7 years, DS = 16,5; Range 2-83), and 114 were males (47,5%, mean age 20,9 years, DS = 12,4; Range 3-73); in all cases, a history of trauma was reported. The ventral surface was the most frequent location (224 cases - 93,3%), and in the great majority (235 cases - 97,9%), pathology revealed mucous spillage with a wall formed by fibrous connective and granulation tissue with no epithelium lining the cavity. Superficial mucocele and sclerosing sialoadenitis were the more frequent pathological variants (21 cases - 8,8%). All lesions were treated with excision and enucleation of the servicing gland. The healing was uneventful in all cases, but there were four recurrences and two cases of sensory paraesthesia of the border of the tongue, all in males, except one case of paraesthesia in a female. Conclusions Tongue mucoceles must be differentiated from many benign and malignant lesions. For this reason, surgical removal of the lesion and of the associated gland with a pathological exam is mandatory. In fact, the anatomical location of the glands and the possible pathological variants must be considered to reach a correct diagnosis and diminish possible relapses. Trial registration CE-Muc_Ton_3/2023.